Efecto de dos fertilizantes foliares en el rendimiento y calidad de Fragaria vesca L. VAR. AROMAS EN QUIRIHUAC, LAREDO – TRUJILLO - Alvarado Avila, Vladimir Bertoni (2016)
Present it investigation developed at the locality of Quirihuac, district Laredo, province of Trujillo, apartment Freedom, for the sake of evaluating two fertilizers foliares in the performance and quality of Fragaria vesca L var and establishing if any one their provide bigger performance and quality comparatively among themselves and to a cultivation without application. The evaluated variables went : Height from the beginning, number of sheets for plant, number of fruits curdled by plant, diameter of the fruit, diameter fruit, weight of fruit, performance and color of fruit. You applied over yourself the design of complete blocks at random with three repetitions. The analysis of variance was executed to the 95 % for the data generated by the evaluations and the proof of significance that presented statistical significance of Tukey for the sources. You met than the product CROP + PLUS to a dose of 2 1 has L you improved characteristics average yield for plant, height from the beginning, number of sheets, diameter from the beginning, average weight of fruit and number of fruits for plant as well as the quality of the strawberry var. Aromas, improving the grade of coloration ( witness of antocianinas ), decreasing the level of quality third and enlarging the strawberry of second quality without demedro of the middleweight of the fruit, besides than fertilization foliating accompanied the performance of the strawberry improves var of a bioestimulante. You perfume, as from the comparison of two fertilizers foliares whose difference is the addition of organic stimulant components in the product CROP + BONUS respect to only mineral FORTE BAYFOLAN's elements.